Analisis Potensi dan Kontribusi Subsektor Peternakan terhadap Sektor Pertanian dan Perekonomian di Indonesia - Melianti Nasution; Firmansyah Firmansyah; Afriani H; Fachroerrozi Hoesni; Dodi Devitriano; Farizal Farizal (Universitas Batanghari Jambi, 2026)
This study aims to determine the potential, contribution, growth, and relationship of subsectors to the agricultural sector and the economy, as well as the differences in potential, contribution, and growth of the livestock subsector to the agricultural sector and the economy. This study was conducted over a one-month period using descriptive quantitative methods using secondary data. The data collected were taken from BPS (Central Statistics Agency). The results of the study show that the potential of the livestock subsector in Indonesia with an average IKS value reaching between 0.0164 to 0.0418, all of which are categorized as